2014
DOI: 10.4103/2141-9248.139355
|View full text |Cite
|
Sign up to set email alerts
|

The city of hope-quality of life-ostomy questionnaire: Persian translation and validation

Abstract: Background:Since there is no disease-specific instrument for measuring quality-of-life (QOL) in Ostomy patients in Persian language.Aim:This study was designed to translate and evaluate the validity and reliability of City of Hope-quality of life-Ostomy questionnaire (COH-QOL-Ostomy questionnaire).Subjects and Methods:This study was designed as cross-sectional study. Reliability of the subscales and the summary scores were demonstrated by intra-class correlation coefficients. Pearson's correlations of an item … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
2
3
0
Order By: Relevance
“…4 Numerous studies have reported that all domains of quality of life were significantly influenced by ostomy-related problems, with social well-being being the most strongly affected domain. 28,32,33 Our finding indicating that social well-being was the most problematic area of quality of life is consistent with previous studies conducted in Iranian, 32 Chinese, 33 Croatian, 28 and even Korean 34 CRC patients with ostomies. Similar to a 2020 study by Konjevoda and colleagues, 28 our results highlighted poorer outcomes for patients' psychological and social well-being compared with their physical and spiritual well-being.…”
Section: N Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…4 Numerous studies have reported that all domains of quality of life were significantly influenced by ostomy-related problems, with social well-being being the most strongly affected domain. 28,32,33 Our finding indicating that social well-being was the most problematic area of quality of life is consistent with previous studies conducted in Iranian, 32 Chinese, 33 Croatian, 28 and even Korean 34 CRC patients with ostomies. Similar to a 2020 study by Konjevoda and colleagues, 28 our results highlighted poorer outcomes for patients' psychological and social well-being compared with their physical and spiritual well-being.…”
Section: N Discussionsupporting
confidence: 92%
“…Ostomy formation can lead to profound impairments in patients’ physical, psychological, and social functioning and ultimately contribute to poor overall quality of life 4 . Numerous studies have reported that all domains of quality of life were significantly influenced by ostomy-related problems, with social well-being being the most strongly affected domain 28,32,33 . Our finding indicating that social well-being was the most problematic area of quality of life is consistent with previous studies conducted in Iranian, 32 Chinese, 33 Croatian, 28 and even Korean 34 CRC patients with ostomies.…”
Section: Discussionsupporting
confidence: 90%
“…QoL, along with relevant sociodemographic and medical characteristics, were assessed using the City of Hope Quality of Life Questionnaire for a Patient With an Ostomy (QOL-O; Grant et al, 2012). The two-part, 90-question QOL-O has been shown to be a valid, reliable, and reducible tool in the U.S., Croatian, and Iranian settings (Anaraki et al, 2014; Grant et al, 2004; Konjevoda et al, 2020). The first section of the QOL-O contains 47 closed- or open-ended questions related to sociodemographic characteristics, employment, sexual activity, psychological support, clothing, diet, and daily ostomy care.…”
Section: Methodsmentioning
confidence: 99%
“…Apart from original tool, various translations are shown to be valid and reliable (Persian, Chinese). [89] Now with this translation and validation in Malayalam language, it is once again proved to be a good tool with transcultural adaptability and validity.…”
Section: Discussionmentioning
confidence: 99%
“…This questionnaire is being successfully translated in many languages including Chinese and Persian. [89] In the present study, we have translated and validated this instrument to local language Malayalam, which is the language spoken by 38.5 million people living in South Indian state, Kerala. Colorectal cancer is one of the diseases which has increased in incidence and caused maximum disability adjusted life years, in India in general and Kerala in particular.…”
Section: Introductionmentioning
confidence: 99%